KINERJA DAN DAMPAKNYA - Sugiarti, Endang (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2020)
Presenting quality in education is a necessity, and the answer is in the teacher An educational institution is known to be good if it’s able to bring achievements to students, and the answer is in the teacher. Therefore, the teacher is the key word in education, so developing is a necessity. This study aims to reveal the lecturers performance, see the conditions and how it impact on institution. Scientific studies using qualitative, how to explain tends to be descriptive, so the real conditions are known. The sample of analysis is data, which is obtained from related institutions in a secondary way. The results showed that the lecturer's performance was low, with a score of 2 (average). The real impact is that institutions find it difficult to get good accreditation. Then, lose the opportunity to build a positive image in the future